The Color-Word Stroop Task Does Not Differentiate Cognitive Inhibition Ability Among Esports Gamers of Varying Expertise - Toth, Adam J.; Kowal, Magdalena; Campbell, Mark J. (Frontiers in Psychology, 2019)
This study set out for the first time to identify whether gamers of low, intermediate and elite skill level in a prominent esports game, Counter-Strike: Global Offensive, demonstrated increasingly superior performance on a test of a specific cognitive skill (cognitive inhibition). Here we tested low, intermediate, and high ranked gamers and compared their performance on a color-word Stroop task and also compared the performance of players in each gaming rank group to non-gamers. Contrary to our hypothesis, the Stroop Task did not differentiate significantly gamers of varying expertise. Although, we found that when considering both accuracy and response times, elite gamers performed significantly better than both intermediate and low ranked gamers on the simple choice reaction time condition and both elite and novice gamers performed significantly better than intermediate ranked gamers on the incongruent condition (a measure of cognitive inhibitory ability).